2009
DOI: 10.1038/ijo.2009.251
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracies in food and physical activity diaries of obese subjects: complementary evidence from doubly labeled water and co-twin assessments

Abstract: Objective: To study whether eating or physical-activity (PA) habits differ between obese and non-obese monozygotic (MZ) co-twins independent of genetic effects. Methods: Rare MZ pairs discordant for obesity (n ¼ 14, body mass index difference 5.2 ± 1.8 kg m -2 ) and weight-concordant control pairs (n ¼ 10, 1.0±0.7 kg m -2 ), identified through a population-based registry of 24-28-year-old twins (n ¼ 658 MZ pairs), completed 3-day food and PA diaries and eating behavior questionnaires. Each twin was asked to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 41 publications
9
58
2
Order By: Relevance
“…We found that obesity and insulin resistance were associated with increased concentrations of MUFAs and lower concentrations of PUFAs, in particular omega-6 FAs and to a lesser extend omega-3 FAs. The serum FA profile is influenced by dietary fat intake over the past few weeks [35], and we have previously reported a lower proportional dietary PUFA intake in the heavier co-twins of the discordant MZ pairs [36]. Rate-limiting enzymes are also important determinants of the serum FA profile; in particular stearoyl-CoA desaturase-1 (SCD-1) synthesizes MUFA from SFA and D6-desaturases synthesizes highly unsaturated FAs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that obesity and insulin resistance were associated with increased concentrations of MUFAs and lower concentrations of PUFAs, in particular omega-6 FAs and to a lesser extend omega-3 FAs. The serum FA profile is influenced by dietary fat intake over the past few weeks [35], and we have previously reported a lower proportional dietary PUFA intake in the heavier co-twins of the discordant MZ pairs [36]. Rate-limiting enzymes are also important determinants of the serum FA profile; in particular stearoyl-CoA desaturase-1 (SCD-1) synthesizes MUFA from SFA and D6-desaturases synthesizes highly unsaturated FAs.…”
Section: Discussionmentioning
confidence: 99%
“…Both facets are difficult to measure in practice, with the former suffering from a clear over-reporting and the latter from under-reporting/under-eating pattern by the obese. 39 Measures of food intake and physical activity were investigated utilizing food and exercise diaries as well as by having each twin to compare Figure 3. Development of BMI from full-term birthday to 23 years in the leaner (dotted lines) and heavier (solid lines) co-twins in MZ twin pairs discordant for obesity in early adulthood; both sexes combined after age-and sex-specific calculation of standardized z-scores based on the British growth reference population.…”
Section: Development Of Obesitymentioning
confidence: 99%
“…The co-twins were asked to rate themselves in relation to their co-twins by questions: 'Which one of you, you or your co-twiny' . Adapted from Pietilainen et al 39 hypertriglyceridemia. Despite the considerable difference in BMI, these 'classical' lipid measurements were not much different between the young, 'healthy' co-twins.…”
Section: Prediabetic Changes In Acquired Obesitymentioning
confidence: 99%
“…Data from animal and human studies in various environments support the theory of a physiologically constrained energy flux [33]. For example, there were no differences in EE or EI between monozygotic twins who differed in PA levels and body composition [34,35]. Similarly, there was no difference in TDEE between members of an Indian tribe living a predominantly sedentary lifestyle with accompanied increased body weight in a U.S. reservation and those following a traditional lifestyle, characterized by high PA and lower body weight in Mexico [26].…”
Section: The Role Of Energy Flux In Weight Managementmentioning
confidence: 79%